2010
DOI: 10.1186/1475-925x-9-46
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of the impedance ratio method used in electronic foramen locators

Abstract: BackgroundThe results of an in vivo study on the "ratio method" used in electronic foramen locators (EFL) are presented. EFLs are becoming widely used in the determination of the working length (WL) during the root canal treatment. The WL is the distance from a coronal reference point to the point at which canal preparation and filling should terminate. The "ratio method" was assessed by many clinicians with the aim of determining its ability to locate the apical foramen (AF). Nevertheless, in vivo studies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Errors related to working length can lead to overinstrumentation and consequent overfilling, inducing the formation of granulomas, impairing the outcome of endodontic treatment, since cytotoxic effects of obturating materials can induce postoperative pain and even persistence of the inflammatory process. 6,7,8 In biopulpectomy, the biological philosophy preserves the vitality of the invaginated periodontal tissue inside the cemental canal (periodontal stump) aiming a periapical repair process. 9,10 Endodont ic l iterat u re suggest s t h at t he consistency and accuracy of the electronic apex locators (EALs) function may vary in the apical foramen and the apical constriction.…”
Section: Introductionmentioning
confidence: 99%
“…Errors related to working length can lead to overinstrumentation and consequent overfilling, inducing the formation of granulomas, impairing the outcome of endodontic treatment, since cytotoxic effects of obturating materials can induce postoperative pain and even persistence of the inflammatory process. 6,7,8 In biopulpectomy, the biological philosophy preserves the vitality of the invaginated periodontal tissue inside the cemental canal (periodontal stump) aiming a periapical repair process. 9,10 Endodont ic l iterat u re suggest s t h at t he consistency and accuracy of the electronic apex locators (EALs) function may vary in the apical foramen and the apical constriction.…”
Section: Introductionmentioning
confidence: 99%
“…In the sequence, the endodontic file that better fitted into the root canal walls at that limit was fixed. Several important researchers ensure that AF represents an anatomic structure more reliable to carry out the eletronical measurements (11,12,15,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies (11)(12)(13)(14)(15) have shown the reliability of new-generation EALs, some models have not been assessed in vivo yet. This is the specific case of the Quill Apex Locator® (Ultradent Products, South Jordan, UT, USA), a third-generation EAL.…”
Section: Introductionmentioning
confidence: 99%